What determines the use of urban green spaces in highly urbanized areas?: examples from two fast growing Asian cities - Schetke, Sophie; Lautenbach, Sven; Kabisch, Nadja (Urban forestry & urban greening, 2016)
The use of urban nature and its correlation with socio-economic and cultural conditions of urban dwellers were subject to a multitude of scientific studies in the last years. Nature and green spaces were found important for relaxing, mental restoration, playing sports and physical activities or simply for being outside together with people. Until now, less is known about spatial settings as determinants for green space use in fast growing major agglomerations in the developing world. Comparative case studies from developing countries could help consolidate a general hypothesis that people living in the same spatial setting (e.g. a highly urbanized city) use urban green spaces and prioritize specific green space facilities in a similar way regardless of developed or developing country. This study addresses this hypothesis by using a questionnaire survey for understanding peoples’ use of urban green spaces in Karachi, Pakistan and Ho-Chi-Minh City in Vietnam. Questionnaire surveys identified perception of and activities in urban green spaces in both cities. In Ho-Chi-Minh City 118 questionnaires were valid for analysis. In Karachi 315 questionnaires were analyzed. Our study shows that the main reason for visiting green spaces is walking and spending time with friends and family. This is mostly done in larger groups for picnics. We also show that accessibility of green spaces is a clear driver of their use by residents. Additionally, residents highlighted the need for urban green spaces but criticized their design and that green spaces lack of basic facilities such as benches or toilets in both cities. Results, thus, partly verify the initial hypothesis, because some green space activities and expected facilities are similar and some are different in developed compared to developing countries. The differences may result from cultural or religious influences and help to broaden the knowledge base on the use of urban green spaces in fast growing Asian cities.